2019
DOI: 10.1002/agm2.12063
|View full text |Cite
|
Sign up to set email alerts
|

Who has the guts to deprescribe proton pump inhibitors? A pharmacist‐led intervention in a long‐term care facility setting

Abstract: Proton pump inhibitors (PPIs) are acid-suppressant drugs that are widely prescribed for a number of gastrointestinal (GI) indications. In 2015, PPIs accounted for Can$253.3 million in public drug program spending in Canada, and were one of the top ten drug classes with the highest spending. 1 Furthermore, pantoprazole was found to be the fifth most common drug prescribed in Canada, with more than 11 million prescriptions dispensed in 2012. 2 With pantoprazole's high prevalence of use, there is a growing concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Continuous education programs for clinicians detailing evidence-based indications for SUP and the adverse reaction of AST are required to correct doctors’ misunderstandings ( Hussain et al, 2010 ; Savarino et al, 2018 ). The intervention of clinical pharmacists could decrease the inappropriate usage of ASMs, as well as drug expenditures and the risk of adverse events, effectively ( Hussain et al, 2010 ; Jarchow-Macdonald and Mangoni, 2013 ; Buckley et al, 2015 ; Masood et al, 2018 ; Tandun et al, 2019 ). Clinical pharmacists could help strengthen regulation of clinical application of PPIs.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous education programs for clinicians detailing evidence-based indications for SUP and the adverse reaction of AST are required to correct doctors’ misunderstandings ( Hussain et al, 2010 ; Savarino et al, 2018 ). The intervention of clinical pharmacists could decrease the inappropriate usage of ASMs, as well as drug expenditures and the risk of adverse events, effectively ( Hussain et al, 2010 ; Jarchow-Macdonald and Mangoni, 2013 ; Buckley et al, 2015 ; Masood et al, 2018 ; Tandun et al, 2019 ). Clinical pharmacists could help strengthen regulation of clinical application of PPIs.…”
Section: Discussionmentioning
confidence: 99%
“…Table summarises the characteristics of the 59 included papers. The majority of studies were located in the United States, UK and Australia with smaller numbers from the Netherlands, Canada and Belgium . Twelve papers reported randomised controlled trials, and five were non‐randomised controlled studies, with the remainder pre‐/post‐uncontrolled interventions conducted as service evaluations.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen papers stated that the pharmacist delivering the service was a ‘consultant’, and twelve papers noted that the pharmacist was described as ‘clinical’ . Five papers reported that the pharmacist had completed an accreditation process, one of which described the training as consisting of consultation skills, identification of drug‐related problems, guidelines and how to create pharmaceutical care plans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There may be a need to explore and implement mechanisms that encourage the systematic and routine practice of assessing ongoing PPI use in general practice. Possible solutions to explore may include: involving other healthcare providers such as nurses or pharmacists [28,29] in initiatives that address PPI use, including expected durations/reassessment dates and indications on initial PPI prescriptions, dedicated consultations for deprescribing, or setting up for systems for triaging PPI refills.…”
Section: Implications For Clinical Practice and Researchmentioning
confidence: 99%